The essential "Star Wars"Philip Pullman's baroque aesthetics - Perrot, Jean (Ondina - Ondine, 2020)
This essay has a twofold purpose: to consider the issues of contemporary Young Adult literature addressed to “the children of the videosphere” within the context of globalized culture and to assess the importance of postmodern Baroque aesthetics in the “Star Wars” system of modern Letters and mass-media. Writers often resort to such aesthetics with the prospect of commercial hegemony, but some of them find their “distinction” (in Pierre Bourdieu’s delineation) through intertextuality – be it avowed or hidden – with the great masters of the past (William Blake and John Milton). We will investigate the secret workshop of Phillip Pullman’s His Dark Materials Trilogy and some of his other works, as well as Jostein Gaarder’s Sophie’s World and diverse literary productions. With their arresting butterflies as significant baroque emblems, these works provide a new and spellbounding vision of the Western hero and offer a new “reterritorialization” of Letters. More particularly, Philip Pullman’s literary gesture has been to extract the baroque message from the vulgarised versions of popular mass media and to give it a new distinction.Key words: Postmodern baroque, William Blake, picaresque, humour, parody, Philip Pullman, Jostein Gaarder.